Truncation of neurokinin-1 receptor—Negative regulation of substance P signaling. Issue 6 (10th January 2018) - Spitsin, Sergei; Pappa, Vasiliki; Douglas, Steven D
Abstract: Substance P (SP) is a tachykinin peptide, which triggers intracellular signaling in the nervous and immune systems, as well as, other local and systemic events. The interaction between SP and its receptor, neurokinin-1 receptor (NK1R), results in major downstream cellular actions, which include changes in calcium fluxes, ERK, and p21-activated kinase phosphorylation and NFκB activation. Two naturally occurring variants of the NK1R, the full-length, 407 aa receptor (NK1R-F) and the truncated, 311 aa isoform (NK1R-T), mediate the actions of SP. Receptor truncation partially disrupts signaling motifs of the carboxyl tail, a critical site for mediating NK1R signaling, resulting in a "less-efficient" receptor. Although NK1R-F is the predominant isoform in the central and peripheral nervous systems, NK1R-T is expressed in several tissues and cells, which include monocytes, NK cells, and T-cells. The SP binding domain is not affected by truncation and this site is identical in both NK1R receptor isoforms. However, while cells expressing NK1R-F respond to nanomolar concentrations of SP, monocyte and macrophage activation, mediated through NK1R-T, requires micromolar concentrations of SP in order to elicit signaling responses. Elevated plasma levels of SP are associated with increased inflammatory responses and NK1R antagonists reduce inflammation and cytokine production in vivo . This mini review presents and discusses the novel hypothesis that the expression of NK1R-T on immune system cells prevents immune activation in a milieu, which usually contains low concentrations of SP and, thus, maintains immune homeostasis. In contrast, in the activated neuronal microenvironment, when SP levels reach the threshold at tissue sites, SP promotes immune activation and modulates monocyte/macrophage polarization. Abstract : The truncated isoform of the neurokinin 1 receptor generated through alternative splicing regulates several biologic functions which include immune and inflammation pathways.